In Vitro and In Silico Analysis of the Bindings between Legacy and Novel Per- and Polyfluoroalkyl Substances and Human Serum Albumin - Yuqing Wu; Jia Bao; Yang Liu; Xin Wang; Xinyi Lu; Ke Wang (Toxics, 2024)
Per- and polyfluoroalkyl substances (PFASs) are emerging contaminants of concern that can enter the human body through a variety of pathways and thereby cause harmful effects. Exposure of pregnant women to PFASs could even affect both the mother and the child. Human serum albumin (HSA) is considered to be the primary transport protein for a variety of substances in body fluids. It can be bound to different contaminants and might result in possible effects on human health. Yet, few studies are available on the binding affinity of legacy PFASs and their novel alternatives to HSA. In this study, the binding mechanisms of HSA to both legacy PFASs and their novel alternatives were investigated using fluorescence spectroscopy, together with further molecular docking. The results show that all the target PFASs were statically quenched against HSA with binding ratios of 1:1. The binding constants of long-chain PFASs and novel alternatives of perfluoroalkanesulfonic acids (PFSAs) were greater than 102, whereas those of short-chain PFASs alternatives and novel alternatives of perfluorocarboxylic acids (PFCAs) were less than 102. In general, the binding affinities of PFCAs on HSA were less than that of PFSAs, while the binding affinities of short-chain PFASs alternatives on HSA were smaller than those of long-chain PFASs and their novel alternatives. Therefore, bindings to HSA could be considered as an important influencing factor for the bioaccumulation of legacy and novel PFASs in the human body.